PHARMACOGNOSTIC CHARACTERISTIC OF KAEMPFERIA GALANGA RHIZOME DRIED BY OVEN AND COMBINATION METHODS - INDRADI, RADEN BAYU; SUSILAWATI, YASMIWAR; RAMADHANIA, ZELIKA MEGA; SAVITRI, ASRI; SOLEH, SOLEH; ZUHROTUN, ADE; ISKANDAR, YOPPI (International Journal of Applied Pharmaceutics, 2022)
Objective: The research objective was to determine the effect of the drying process on the pharmacognostic characteristic of dried Kampferia galanga produced in the Post-Harvest Processing Center of Medicinal Plants facility. Methods: The drying methods were oven-based drying in 80 °C temperature and a combination-based drying process, which included greenhouse drying for 6-8 h and transfered to 80 °C oven. The pharmacognostic characteristic of products were evaluated based on Indonesian Herbal Pharmacopeia standard, which included macroscopic and microscopic evaluation, thin-layer chromatography, water and ethanol soluble content, total ash and acid-insoluble ash content, volatile oil content, ethyl para-methoxycinnamate content, total plate count, and total yeast and mold count. Results: The result showed dried K. galanga from both drying methods met the quality standard. Interestingly, the combination-based methods possed 6-7 h quicker in drying time compared to oven-based methods despite lower temperatures was used at the greenhouse. Conclusion: It can be concluded that both methods could retain the quality of K. galanga rhizome.